A Hybrid Green Lean Supply Chain Framework for the Thai Manufacturing Industry - Suddee, Salinla (2015)
Typically, Thai organisations implementing lean practices aim to maximise operational efficiency, resulting in cost reductions. However, since globalisation and pressures from stakeholders have forced Thai manufacturing firms to take more responsibility towards the environment and societies, sustainability has become one of the big themes in lean management practices. Therefore, the purpose of this study is to explore whether lean practices can enhance sustainable firm performance in terms of economic and environmental dimensions. In addition, while most organisations in developing countries such as Thailand largely focus on economic performance as a priority, implementing green supply chain management (GSCM) into operations systems seems to provide a sense of insecurity for managers. This study also investigates how GSCM practices moderate the relationship between lean practices and sustainable firm performance. The empirical data are collected from 211 respondents in Thai manufacturing organisations and analysed by using a moderated hierarchical regression; semistructured interviews are also employed to reconfirm the results. The findings suggest that lean practices seem to provide a win-win opportunity for Thai manufacturing companies to sustain their business in terms of economic and environmental performance. We also find that embedding internal GSCM into operational practices as a hybrid system can significantly enhance environmental performance. However, the results of such a system does not confirm the economic performance so that, at this point in time, integrating GSCM practices into operations management is not likely to be economically attractive for the Thai manufacturing industry. In particular, the results also highlight the fact that an environmental collaboration between suppliers and customers lacks the attention of Thai manufacturers. This implies that being a leader in these practices may offer a great opportunity for Thai manufacturers to achieve competitive advantages over competitors in the same industry.